الإمام المرحومي واستدراكاته على الخطيب من خلال حاشيته على الخطيب: Imam al-Marhoomi and His Perspectives on al-Khatib Through His Retinue on al-Khatib - Al-Deirchawi, Khaled; Abdul Khalil, Shahidra; Ali, Abdul Karim (Online Journal of Research in Islamic Studies, 2019)
There is no doubts that the study of manuscripts is important in Islamic studies, especially if it is needed by Muslims in their life. The importance of this research comes from its subject which is Fiqh and matters of Halal and Haram where every Muslim is obliged to follow. The research aims to highlight the biography of Al-Imam Al-Marhoomi and the approach he applied in his book in general, and his corrections to the Khatib Al-Sherbini in particular. The researcher followed in this research both approaches of descriptive and Analytical to extract the relevant issues. The researcher concluded the scientific value of the book in general, and its methodology in comments and corrections in particular, because of its scientific benefits, and guiding students to the mechanism of research and right understanding of the opinions of jurists to balance them in critical way.